Purifying dirty computers: cyborgs, sex, Christ, and otherness - Ott, Kate M. (Cursor_, 2023)
Virtual reality, especially neural network technology, provides a theologically imaginative experience of otherness that disrupts racialized, sexual, and cultural logics that undergird dominant Christian white cisheterosexual theologies. These technologies not only enable users to "walk a mile in another's shoes" or the other they wish they were, users feel, embody, and are other in ways only hinted at by Jesus' hybrid existence proposed in Matthew 25: 35-46. I use a digital sexual storytelling method to explore an indecent incarnational theology of the cyborg which uncovers the persistence of anti-blackness and anti-queerness in digital Christain theology as well as evidences strategies of indecency to combat them.